(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The article highlights the problems observed in the process of mastering the technical and tactical training of young students in football classes and clubs. Recommendations are given to effectively solve these problems.